USAGE INTENTION IN APP-BASED BANKING: AN EMPIRICAL STUDY USING AMOS - Himani; Kant, Ravi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines the principal elements that affect users’ proclivities towards the usage of application-based banking systems. A theoretical framework was formulated to discern the most pivotal determinants of usage intention. Empirical data were gathered via a structured Google Form, and subsequent statistical analyses were performed utilizing SPSS and AMOS software. Exploratory Factor Analysis (EFA) was employed in SPSS version 26 to delineate pertinent factors and assess their impact on users’ intentions. The research model investigated the interrelations among Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Social Influence (SI), and the intention to engage with app-based banking. The outcomes underscore PEOU as the predominant predictor of intention, trailed by PU, whereas SI was not observed to exert a significant influence.